THE WELL‐BEING OF NATIONS: ESTIMATING WELFARE FROM INTERNATIONAL MIGRATION. (8th April 2021) - Lee, Sanghoon; Lee, Seung Hoon; Lin, Jeffrey
Abstract: The limitations of GDP as a measure of welfare are well known. We propose a new method of estimating the well‐being of nations. Using gross bilateral international migration flows and a discrete choice model in which everyone in the world chooses a country in which to live, we estimate each country's overall quality of life. Our estimates, by relying on revealed preference, complement previous estimates of well‐being that consider only income or a small number of factors, or rely on structural assumptions about how these factors contribute to well‐being.